Pola Kuman Hasil Pemeriksaan Kultur di RSUD Siti Fatimah Kota Palembang, Sumatera Selatan, Indonesia: Hasil Penelitian - Husada, Dedi Yanto; Eviningtyas, Ririn (Cermin Dunia Kedokteran, 2025)
Introduction: Bacterial culture examination is the diagnostic standard for various infectious diseases. This descriptive research aims to determine the microorganism pattern in culture examinations at Siti Fatimah Regional Hospital, Palembang, South Sumatra, Indonesia. Methods: Secondary data were from records of microorganism culture examination results at the Clinical Pathology Laboratory of Siti Fatimah Regional Hospital, South Sumatra Province, from January to December 2022. Result: During that period, 217 samples were collected from various sources: 64 (29.5%) blood samples, 25 (11.5%) urine samples, 47 (21.7%) pus samples, 64 (29.5%) sputum samples, and 17 (7.8%) body fluid samples. Most samples’ characteristics were from patients who were >18-60 years old, male, and non-intensive inpatient ward patients. A total of 137 (63.1%) samples showed positive growth, mostly from sputum (60 samples; 93.8%), with the majority of bacteria being Klebsiella pneumoniae (11 samples; 18.3%). The most frequently detected bacteria in blood and urine cultures was Pseudomonas aeruginosa, in 5 samples (29.5%) and 3 samples (27.3%), respectively. Staphylococcus aureus was largely seen in pus (8 samples; 20%) and body fluid (3 samples; 33.3%) cultures. Conclusion: The results of the culture examination showed that most positive germ growth came from sputum, with the most bacteria found being Pseudomonas aeruginosa, Staphylococcus aureus, and Klebsiella pneumoniae.